Antimicrobial efficacy of methylene blue-functionalized graphene oxide-mediated photodynamic therapy against Enterococcus faecalis in root canal disinfection - Rizwan Jouhar, FCPS; Mohamad Syahrizal Halim, M.Rest.Dent; Sayed A. Quadri, MD; Muhammad Adeel Ahmed, PhD; Faheem Shah, PhD (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: هدفت هذه الدراسة إلى تقييم الفعالية المضادة للميكروبات للعلاج الضوئي الديناميكي باستخدام الميثيلين الأزرق المؤكسد الجرافين المختزل مقابل تأثير الميثيلين الأزرق التقليدي لتقييم قدرات الحدوث ضد بكتيريا المكورات المعوية البرازية (Enterococcus faecalis). طرق البحث: في هذه الدراسة المختبرية تم تنمية أغشية حيوية متعددة بكتيريا المكورة المعوية على 105 أسنان ذات (CFU). جذر واحد بعد إيداع البلاك لمدة 21 يوماً تم تقييم حيوية البكتيريا من خلال تحليل وحدات تكوين المستعمرات. تم تقسيم العينات إلى ست مجموعات تجريبية متساوية. عولجت المجموعات إما بمحلول 5% هيبوكلوريت الصوديوم (المجموعتان 1 و2)، أو بالعلاج الضوئي الديناميكي المعتمد على أزرق الميثيلين (المجموعتان 3 و4)، أو بالعلاج الضوئي الديناميكي المعتمد على أزرق الميثيلين المؤكسد بالجرافين (المجموعتان 5 و6). تم استخدام الليزر بسرعة 6000 دورة في الدقيقة، بينما تمت إضافة 200 ميكرولتر من المحلول الملون في كل مجموعة. النتائج: لوحظ انخفاض كبير في الحمل البكتيري في جميع المجموعات التجريبية. بيّنت أعلى نسبة تقليل: (99.9%) في المجموعة 6 (الميثيلين الأزرق المؤكسد المختزل بالجرافين + الليزر). المجموعة 4 (الميثيلين الأزرق + الليزر) أظهرت تقليل (96.6%)، والمجموعة 2 (هيبوكلوريت الصوديوم + الليزر) أظهرت تقليل (99.9%). بينما المجموعة 1 (هيبوكلوريت الصوديوم فقط) أظهرت نسبة تقليل (99.9% ± 33.33%)، والمجموعة 3 (الميثيلين الأزرق فقط) أظهرت (99.9% ± 33.33%). أقل نسبة تقليل لوحظت في المجموعة 1 هي (99.83%) دون أي فعالية سلبية. الاستنتاجات: حقق الميثيلين الأزرق المؤكسد بالجرافين (MB/rGO) مع التفعيل الصوتي والليزري أعلى نسبة في خفض الحمل البكتيري، وتلاه مباشرة العلاج الضوئي الديناميكي المعدل باستخدام الميثيلين الأزرق. كان ريّ قناة الجذر بهيبوكلوريت الصوديوم فعالاً، لكنه لم يُظهر نتائج سالبة في الزرع البكتيري. تؤكد نتائجنا إمكانات العلاج الضوئي الديناميكي المعدل كخيار معزز لتحسين تنظيف قنوات الجذر. Abstract: Objective: This study assessed the antimicrobial efficacy of photodynamic therapy (PDT) using functionalized graphene oxide with methylene blue (MB/rGO) to achieve root canal disinfection against Enterococcus faecalis. Methods: In this in vitro study, E. faecalis biofilms were developed on 105 single-rooted teeth after decoronation over 21 days. Bacterial viability was assessed with colony forming unit (CFU) analysis. Six experimental groups with equal numbers of samples (n = 15) were treated with 5 % NaOCl (groups 1 and 2), MB-based PDT (groups 3 and 4), or MB/rGO-based PDT (groups 5 and 6). Sonic activation (groups 2, 4, and 6) was performed at 6000 cpm for 2 min, whereas laser activation (groups 3–6) was performed with a 650 nm, 200 mW laser for 2 min. Post-treatment CFU/mL counts and bacterial reduction percentages were recorded. Results: A substantial reduction in bacterial load (p < 0.001) was observed across all experimental groups. The highest decrease (99.99 %) was observed in group 6 (modified PDT with MB/rGO), which also had the lowest CFU (1.21 × 103/mL) and the highest negative culture rate (40 %). Group 4 (modified PDT with MB) showed similar efficacy (99.99 % decrease, 33.33 % negative cultures), whereas NaOCl irrigation (group 1) showed the smallest decrease (99.83 %) and no negative cultures. Conclusion: Functionalized MB/rGO with sonic and laser activation achieved the highest bacterial load decrease, and was closely followed by modified PDT with MB. NaOCl irrigation was effective but did not yield negative cultures. Our findings highlight the potential of modified PDT for enhanced root canal cleaning.